1995
DOI: 10.1289/ehp.95103272
|View full text |Cite
|
Sign up to set email alerts
|

Half-life of polybrominated biphenyl in human sera.

Abstract: (12).The purpose of this study was to estimate the half-life of PBB in human blood sera in order to contribute to our understanding of how continued body burden relates to the possible adverse health consequences of exposure. We found only one previous report of the half-life of PBB in humans (13). This study gave a median estimate of 12 years with a range of 4.6-94.7 years. This estimate was determined by serum measurements from 15 females and 12 males; the half-life for females and males was similar. An expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
2
15
2
Order By: Relevance
“…Rosen and colleagues (13) reported a mean half-life of 13.0 years (CI, 6.3-infinite) and median half-life of 18.5 years (CI 9.5-40.1). Differences in inclusion criteria may account for the differences in half-life found in this study as compared to that found by Rosen et al (13), who used only samples taken before 1983. Rosen et al (13) had a sample size of 51, with a maximum of four measurements for any one participant and a 6-year maximum time between measurements.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Rosen and colleagues (13) reported a mean half-life of 13.0 years (CI, 6.3-infinite) and median half-life of 18.5 years (CI 9.5-40.1). Differences in inclusion criteria may account for the differences in half-life found in this study as compared to that found by Rosen et al (13), who used only samples taken before 1983. Rosen et al (13) had a sample size of 51, with a maximum of four measurements for any one participant and a 6-year maximum time between measurements.…”
Section: Discussioncontrasting
confidence: 60%
“…The unmetabolized PBB153 and its analogous PCB congener have an average half-life of at least 10 years (13,33). PBB, like other highly persistent chemicals, is therefore assumed to be in equilibrium among the organs and tissues before substantial amounts are eliminated (34) and was likely in equilibrium before the first serum measurements were taken in That longer half-lives were found with higher initial PBB levels suggests that PBB elimination may be a saturable process at higher exposures resulting in different distribution patterns or, more likely, that there are unmeasured sources of variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The weighted model did not show meaningful changes in the parameter estimates obtained in the unweighted decay model. This is in agreement with Blanck et al (2000a) and Rosen et al (1995) who reported minimal changes when they weighted their models in a similar manner.…”
Section: Discussionsupporting
confidence: 91%